Perspektif Mahasiswa UNISKI Terhadap Fenomena Budaya Korea (Korean Wafe) dan Budaya Lokal (Local Wisdom) - Erlande, Rike; Sari, Novita (Institut Agama Islam Negeri Ponorogo, 2023)
ABSTRACTThe current rapid flow of globalization makes foreign culture enter through several media platforms without any filtering. Including Korean culture that enters and spreads among teenagers. Popular culture of the Korean wave or better known as the